2008
DOI: 10.1038/sj.bjp.0707610
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1‐induced interleukin‐6 synthesis is mediated by the neutral sphingomyelinase/Src kinase pathway in neurones

Abstract: Background and purpose: Interleukin (IL)-1 is a key mediator of inflammatory and host defence responses and its effects in the brain are mediated primarily via effects on glia. IL-1 induces release of inflammatory mediators such as IL-6 from glia via the type-1 receptor (IL-1R1) and established signalling mechanisms including mitogen-activated protein kinases and nuclear factor kappa-B. IL-1 also modifies physiological functions via actions on neurones, through activation of the neutral sphingomyelinase (nSMas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 45 publications
0
43
0
1
Order By: Relevance
“…the local peritoneal endometriosis-associated immunoinflammatory reaction. In addition, several studies showed that IL1b activates other transcription factors including activator protein-1 and cyclic AMP response element binding protein (45,46) and it will be very interesting to investigate the involvement of these factors in MIF regulation. Recent data also showed that the promoter of MIF contains putative binding sites for these two transcription factors (47) and that cyclic AMP response element binding protein positively regulates MIF promoter activity (48).…”
Section: Figurementioning
confidence: 99%
“…the local peritoneal endometriosis-associated immunoinflammatory reaction. In addition, several studies showed that IL1b activates other transcription factors including activator protein-1 and cyclic AMP response element binding protein (45,46) and it will be very interesting to investigate the involvement of these factors in MIF regulation. Recent data also showed that the promoter of MIF contains putative binding sites for these two transcription factors (47) and that cyclic AMP response element binding protein positively regulates MIF promoter activity (48).…”
Section: Figurementioning
confidence: 99%
“…We have reported previously that IL-1 ␣ and IL-1 ␤ induce glial cell production of IL-6 via activation of the mitogen-activated protein kinases (MAPKs), extracellular signal-regulated kinase 1/2 (ERK1/2), p38 and c-Jun N-terminal kinase [9,10] . Neuronal cells also respond to IL-1 to produce IL-6, which is mediated in part by the Src kinase signaling pathway [11] . Although the signaling mechanisms of IL-1 in glial cells are generally well characterised, the precise Interleukin-1 Signaling in Neurons Neurosignals 2011;19:222-230 223 signaling mechanism of IL-1 in neurons remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that neurons produce cytokines has been accepted recently [26] . For instance, studies conducted in vitro have documented that fetal rat dorsal root ganglion neurons produce IFN-␥ and express its receptor [27,28] .…”
Section: Local Availability Of Cytokines In the Cnsmentioning
confidence: 99%